(untitled) (Confluenţe Bibliologice, 2024)
This article presents an overview of the event organized on June 19, 2024, by the Departmental Librarianship Center of the Scientiﬁc Library of the USARB. The event brought together librarians from pre-university educational institutions in the northern region of the Republic of Moldova, including the municipality of Bălți. The primary objective of the meeting was to facilitate the exchange of experiences and best practices among librarians to modernize educational and library services. The workshop focused on identifying challenges faced by school libraries and promoting innovative initiatives in the ﬁeld of library economics. Additionally, success stories from libraries in the municipality of Bălți were showcased during the event.